2009
DOI: 10.2337/dc08-1943
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Overweight During Childhood in Offspring of Parents With Type 1 Diabetes

Abstract: OBJECTIVE -To study which perinatal factors affect the risk of childhood overweight in offspring with a first-degree relative (FDR) with type 1 diabetes and to determine whether maternal diabetes is an independent contributor to overweight risk.RESEARCH DESIGN AND METHODS -Data on a child's weight and height were collected at age 2, 5, and 8 years from 1,214 children participating in the prospective BABYDIAB study. All children had an FDR with type 1 diabetes, including 783 whose mothers had type 1 diabetes. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 23 publications
5
43
1
2
Order By: Relevance
“…Hummel et al [51] reported odds ratios for overweight of 1.1 (0.7, 1.9) (unadjusted) and 0.8 (0.5, We also show a correlation between the difference in mean BMI of diabetic and non-diabetic mothers and the difference in mean offspring BMI z score. These data might be interpreted as indicating that the relationship between maternal and offspring BMI in childhood is due to a common genetic potential and/or a shared postnatal obesogenic environment, rather than intrauterine programming secondary to maternal glycaemia of lesser degree than in overt diabetes (for which maternal BMI is a proxy).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Hummel et al [51] reported odds ratios for overweight of 1.1 (0.7, 1.9) (unadjusted) and 0.8 (0.5, We also show a correlation between the difference in mean BMI of diabetic and non-diabetic mothers and the difference in mean offspring BMI z score. These data might be interpreted as indicating that the relationship between maternal and offspring BMI in childhood is due to a common genetic potential and/or a shared postnatal obesogenic environment, rather than intrauterine programming secondary to maternal glycaemia of lesser degree than in overt diabetes (for which maternal BMI is a proxy).…”
Section: Discussionsupporting
confidence: 51%
“…Two additional studies were identified through a search of forward citations [15,48] and four [49][50][51][52] from hand-searching the reference lists of included papers, giving 34 papers in total. Five cohorts were reported in more than one paper, so only the study that reported the outcomes at an age closest to the overall median age of all studies (7 years) was included in the meta-analysis; 10 papers were excluded on this basis [25, 35, 36, 38-40, 42, 47-49].…”
Section: Resultsmentioning
confidence: 99%
“…5,6,8 Greater weight at birth is related to the risk for developing insulin resistance, obesity, and type 2 diabetes mellitus in the future. 10 Associated with diabetes mellitus are dyslipidemias, which are considered determining factors for the development of cardiovascular diseases. Elevated concentrations of plasma triglycerides, total cholesterol, and low-density lipoprotein (LDL) cholesterol along with decreased highdensity lipoprotein (HDL) cholesterol levels lead to a group of risk factors called the metabolic syndrome, which increases the risk for vascular diseases.…”
Section: Introduction Dmentioning
confidence: 99%
“…These parameters together may be conducive to the occurrence of the metabolic syndrome, which increases the risk for development of vascular diseases. 12,13 The genus Passiflora is largely found in Brazil and include several native plants known as maracujá (yellow passion), but only two of them have commercial importance: Passiflora edulis, usually called juice maracujá, and Passiflora alata, called sweet maracujá. Passiflora quadrangularis has been shown to have hemolytic activity like hemolysin.…”
Section: Introductionmentioning
confidence: 99%